PENGEMBANGAN MODEL PEMBELAJARAN QAWAID SHARRAF DENGAN PENDEKATAN QIYASIYAH di MTs NEGERI SUMBER BUNGUR PAMEKASAN - Achmad Muhlis (Research Institute and Community Engagement of IAIN MADURA, 2016)
The research focuses that will be discussed are the description of learning model, students responses, and factors influencing the development of qawaid sharraf learning model by using qiyasiyah approach. Based on the research result, it has been identified that there are four type of learning model that have been intensively and effectively applied to achieve better qualified learning. They are: firstly, basic competence and learning indicator based learning model; secondly, wazan memorizing by providing example of wazan fi’il madhi on the basis of thariqah tashrif bina’ shahih; thirdly, applying tashrif models on the al-Qur’an pronunciation. There are optimal and positive responses of students toward the development of qawaid sharraf learning model by using qiyasiyah approach, it is supported by the following indicators: (1) motivation emergence, (2) students learning interest increase, (3) students learning competence development, (4) the starting point of Arabic language improvement. In general, the main factor influencing the development of qawaid sharraf learning model by using qiyasiyah approach is the professional planning and process. However, there are several components that are able to endorse the efforts: (1) qualified schools management, (2) students recruitment, (3) teachers competence.